Diagnostic and prognostic value of human prion detection in cerebrospinal fluid. Issue 1 (January 2017) - Foutz, Aaron; Appleby, Brian S.; Hamlin, Clive; Liu, Xiaoqin; Yang, Sheng; Cohen, Yvonne; Chen, Wei; Blevins, Janis; Fausett, Cameron; Wang, Han; Gambetti, Pierluigi; Zhang, Shulin; et al.
Abstract : Objective: Several prion amplification systems have been proposed for detection of prions in cerebrospinal fluid (CSF), most recently, the measurements of prion seeding activity with second‐generation real‐time quaking‐induced conversion (RT‐QuIC). The objective of this study was to investigate the diagnostic performance of the RT‐QuIC prion test in the broad phenotypic spectrum of prion diseases. Methods: We performed CSF RT‐QuIC testing in 2, 141 patients who had rapidly progressive neurological disorders, determined diagnostic sensitivity and specificity in 272 cases that were autopsied, and evaluated the impact of mutations and polymorphisms in the PRNP gene, and type 1 or type 2 human prions on diagnostic performance. Results: The 98.5% diagnostic specificity and 92% sensitivity of CSF RT‐QuIC in a blinded retrospective analysis matched the 100% specificity and 95% sensitivity of a blind prospective study. The CSF RT‐QuIC differentiated 94% of cases of sporadic Creutzfeldt–Jakob disease (sCJD) MM1 from the sCJD MM2 phenotype, and 80% of sCJD VV2 from sCJD VV1. The mixed prion type 1‐2 and cases heterozygous for codon 129 generated intermediate CSF RT‐QuIC patterns, whereas genetic prion diseases revealed distinct profiles for each PRNP gene mutation. Interpretation: The diagnostic performance of the improved CSF RT‐QuIC is superior to surrogate marker tests for prion diseases such as 14‐3‐3 and tau proteins, and together with PRNP gene sequencing the test allows the major prion subtypes to be differentiated in vivo. This differentiation facilitates prediction of the clinicopathological phenotype and duration of the disease—two important considerations for envisioned therapeutic interventions. ANN NEUROL 2017;81:79–92